1998
DOI: 10.1016/s0022-5223(98)70163-1
|View full text |Cite
|
Sign up to set email alerts
|

Large encircling cryoablation without mapping for ventricular tachycardia after anterior myocardial infarction: Long-term outcome

Abstract: One can achieve good results without intraoperative mapping in the treatment of patients with ventricular tachycardia after anterior myocardial infarction by using large encircling cryoablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Reduction of LV cavity size with septal and scar exclusion will prevent functioning of the re-entry circuit; [8] and we believe that adequate endocardium resection and large encircling cryoablation during aneurysmectomy will provide a higher electrical success rate [5,9] This concept must be tested, since overall mortality was comparably low in a recent patient cohort from the RESTORE group [27], that did not undergo PVS evaluation, with the exception of Monaco Cardiothoracique Center patients in that effort. However, the late deaths reported by Athanasuleas are more common in dilated hearts, and were presumably from arrhythmias [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of LV cavity size with septal and scar exclusion will prevent functioning of the re-entry circuit; [8] and we believe that adequate endocardium resection and large encircling cryoablation during aneurysmectomy will provide a higher electrical success rate [5,9] This concept must be tested, since overall mortality was comparably low in a recent patient cohort from the RESTORE group [27], that did not undergo PVS evaluation, with the exception of Monaco Cardiothoracique Center patients in that effort. However, the late deaths reported by Athanasuleas are more common in dilated hearts, and were presumably from arrhythmias [27].…”
Section: Discussionmentioning
confidence: 99%
“…To address this devastating arrhythmic complication, in the pre-implantable cardioverter defibrillator (ICD) era, several surgical techniques were developed for ventricular tachyarrhythmias (ventricular arrhythmias), including aneurysmectomy alone [1][2][3][4], mapping or non mapping-guided endocardial resection with or without LV aneurysmectomy [5][6][7][8], catheter ablation [9], revascularization alone [10]. However, frequency of recurrence, complexity of mapped guided interventions, high rate of sudden death from spontaneous and inducible ventricular tachycardia (VT) in post infarction patients, identified a problem of post-infarction ventricular arrhythmias treatment that was not treated adequately by these approaches to potentially lethal ventricular arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Matthias and Bechtel et al investigating the surgical results of 147 patients treated by anterior LV aneurysm resection without concomitant anti-arrhythmic procedures demonstrated that sudden arrhythmic death occurred in 36.8% of deceased patients during 5 years of follow-up [32]. In this regard, LV aneurysm resection should be supplemented with one of the surgical procedures directed at destruction or isolation of arrhythmogenic focuses when VT is inducible by preoperative electrophysiologic study (EPS) or presents spontaneously, which includes circular endocardial ventriculotomy [35], subtotal endocardial scar resection [36][37][38], endocardial cryoablation [39][40][41] or laser photocoagulation [42,43]. By now, several authors have reported satisfactory results of anti-arrhythmic surgery in patients with LV postinfarction aneurysm at long-term after operation [30,37,44].…”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…In the study of Frapier et al the freedom from VT was 77% at 5 and 7 years after surgery [7]. Demaria et al reported long-term results of encircling cryoablation in a cohort of 52 patients without mapping.…”
Section: Discussionmentioning
confidence: 99%